2013
DOI: 10.1108/igdr-04-2012-0019
|View full text |Cite
|
Sign up to set email alerts
|

What explains the high capital intensity of Indian manufacturing?

Abstract: Purpose – This study aims to focus on the role of labor regulation and credit market imperfections, in addition to that of factor endowments, in determining capital intensities in Indian manufacturing. Design/methodology/approach – The paper considers an alternative approach to identifying the effects of India ' s labor regulations on industrial performance. In particular, the paper uses a measure of the stringency of labor regulations across countries – one that is completely independent of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Our analysis in this paper shows a phenomenal decline in the share of middle skilled routine-task intensive manufacturing jobs that underlines the substantial increase in automation. Hasan et al (2013) have shown that the Indian manufacturing sector uses more capital-intensive technology as compared to other countries at similar levels of development with similar factor endowments. It has been repeatedly argued that policy-induced labour market rigidities have forced Indian manufacturing firms to opt for more capital-intensive technology.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Our analysis in this paper shows a phenomenal decline in the share of middle skilled routine-task intensive manufacturing jobs that underlines the substantial increase in automation. Hasan et al (2013) have shown that the Indian manufacturing sector uses more capital-intensive technology as compared to other countries at similar levels of development with similar factor endowments. It has been repeatedly argued that policy-induced labour market rigidities have forced Indian manufacturing firms to opt for more capital-intensive technology.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…to workers (such as wages and pension provisions), layoffs, retrenchments, and closures. 7 As a consequence, India's labor laws (exemplified by the IDA) has reduced the incentive of firms in the modern manufacturing sector to hire workers on permanent contracts and pushed them toward more capital-intensive modes of production, than warranted by existing costs of labor relative to capital (Saha, Sen, and Maiti 2013;Dougherty 2009;Hasan, Mitra, and Sundaram 2013). In addition, India's restrictive labor laws have had a negative effect on the growth of the formal manufacturing sector, especially its labor-intensive industries, leading to limited possibilities for the formal manufacturing sector to absorb the high levels of surplus labor that are present in a relatively low-productivity agriculture sector (Besley and Burgess 2004;Gupta, Hasan, and Kumar 2009).…”
Section: Labor Regulationsmentioning
confidence: 99%
“…There are several factors that explain the high capital intensity in India's manufacturing compared to countries at similar levels of development and with similar factor endowments (Hasan, Mitra, and Sundaram 2013). Among these, labour freedom and capital market development are important determinants of the capital intensity of production.…”
Section: Capital Intensitymentioning
confidence: 99%